Care, comfort, and capacity: The importance of being flexible in research with Disabled and chronically ill people - Poppy Budworth (Elsevier, 2023)
Flexible research approaches, which account for the uncertainties of everyday life, have long been utilised by Crip Theorists and Critical Disability Scholars. The uptake of such adaptive, flexible approaches has grown further since the start of the COVID-19 crisis due to safety measures which restricted face-to-face work and social gatherings. This paper pushes for an invigorated embrace of bendable remote methods which prioritise the comfortabilities and capacities of Disabled and chronically ill participants. Through examples from ongoing research in the UK with young 'Ostomates', the paper reflects on the design, recruitment, and utilisation of flexible interview and diary methods when researching remotely with young people living with an ileostomy or colostomy. A flexible approach allows participants to choose an interview and diary format (for example, typed, handwritten, audio/video recorded, photographed, text-messaged, phone or Zoom call) as well as the length, date, and time of the task. Further to this, participants decide whether to contribute to the research synchronously in an interview conversation, or asynchronously 'over-time'. Flexibility across the research design provides a way to think about and 'do' traditional research methods differently; and a 'cripping' of research time and practice responds to the embodied and fluctuating nature of chronic illness. Acknowledging and working with participants' individual personalities, responsibilities, skills, and preferences opens research to people who might otherwise be excluded, and as such, amplifies their voices and experiences. This paper recommends a flexible approach to qualitative health research as a 'care-full' response to the complexity of participants' everyday lives.